Peningkatan Hasil Belajar Siswa Melalui Model Discovery Learning pada Siswa Kelas XI TMP A SMKN 3 Palu - Saleh, Muh. (Jurnal Kreatif Online, 2020)
This study aimed to describe the learning outcomes of class XI TMP A SMKN 3 Palu through the Discovery learning model. This type of research was classroom action research with descriptive methods. This research consisted of pre-cycle, cycle I and cycle II. Each cycle consists of 4 stages; planning, implementing, observing and observing. This research was conducted in the odd semester of the 2019/2020 academic year at SMKN 3 Palu. The role of the researcher in this study was as a vocational teacher at TMP. The subjects in this study were 32 male students of class XI TMP A. The data were collected using a test. To measure the success of the research, research success indicators were used, which was student learning outcomes which considered complete if individually on the evaluation results obtained a value of â‰¥ 75. While classical completeness was achieved if all students in the class had completed learning â‰¥ 80%. Based on the research results obtained in the pre-cycle students who completed as many as 12 people with a percentage of 37.5% completeness. In the first cycle it increased, with 22 students completing with a passing percentage of 68.75%. In cycle II, there was an increase again with 26 students who completed and the percentage of completeness was 81.25%. Based on these data, it can be concluded that the discovery learning model can improve the learning outcomes of class XI TMP A SMKN 3 Palu in vocational theory subjects.